THROMBOSIS OF LEFT ATRIAL APPENDAGE DURING THERAPY WITH DIRECT ORAL ANTICOAGULANT. CLINICAL CASE - I. S. Daaboul; S. Yu. Koroleva; A. A. Kudrjavtseva; A. A. Sokolova; D. A. Napalkov; V. V. Fomin (Рациональная фармакотерапия в кардиологии, 2018)
The article presents a clinical observation of the left atrial appendage thrombosis in a 51-year-old female patient with a paroxysmal form of nonvalvular atrial fibrillation which occurred despite long-term anticoagulant therapy with apixaban in a full dose (5 mg b.i.d.), and the patient’s management. The patient was admitted with recurrent symptomatic paroxysm for more than 48 hours, because of which, in accordance with the recommendations, transesophageal echocardiography was performed before an emergency rhythm restoration. Thrombus in the left atrial appendage 0.5×1.03 cm in size was detected. It was decided to refrain from the immediate restoration of the rhythm due to the very high risk of thromboembolic complications. In connection with the categorical refusal of the patient from warfarin, it was decided to replace apixaban with another direct oral anticoagulant – dabigatran 150 mg bid for a period of 4 weeks followed by performing a control transesophageal echocardiographic study. As a result, no thrombus was found on control echocardiography. The particularity of this observation is concomitant hypertrophic cardiomyopathy and diabetes mellitus type 1 in this patient.